Haematological and Serum Biochemical Indices of Sheep in Semi-Arid Environment of Northern Nigeria (Global Journal of Science Frontier Research, 2014)
The hematological and biochemical parameters of 140 apparently healthy sheep consisting of 70 adults (35male and 35 female) comprised of 3 indigenous and popular brzzeeds of sheep of northern Nigeria were studied. Data were analyzed for the effect of breed, sex and season packed cell volume (PCV) was significantly higher (P
Keywords: hematology; blood chemistry; breeds; sheep; lamb; ewe; ram